2019
DOI: 10.3892/mmr.2019.10435
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑20 induces methylation of hepatitis B virus covalently closed circular DNA in human hepatoma cells

Abstract: Methylation was suggested to suppress the transcriptional activity of hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) in hepatocytes. This may be associated with its low replicative activity during the inactive stage of chronic HBV infection; however, the exact mechanisms of methylation in HBV infection remain unknown. We have previously shown that short hairpin RNAs induced the methylation of the HBV genome in hepatoma cell lines. We also reported that the microRNA (miR) 17–92 cluster negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The present study hypothesized that cccDNA methylation may also contribute to the IFN-mediated transcriptional suppression of HBV. To test this hypothesis, our previous cell-based model was used to generate a condition for cccDNA methylation, with some modifications ( 39 ). First, direct infection with wild-type HBV virions ( 52 , 53 ) was used instead of plasmid-mediated in vitro HBV models ( 30 ), because CpG-containing plasmids may trigger inflammatory cytokine responses and become inadvertently methylated ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study hypothesized that cccDNA methylation may also contribute to the IFN-mediated transcriptional suppression of HBV. To test this hypothesis, our previous cell-based model was used to generate a condition for cccDNA methylation, with some modifications ( 39 ). First, direct infection with wild-type HBV virions ( 52 , 53 ) was used instead of plasmid-mediated in vitro HBV models ( 30 ), because CpG-containing plasmids may trigger inflammatory cytokine responses and become inadvertently methylated ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since HepG2 cells were maintained in the presence of fetal bovine serum (FBS) throughout the experiments, the possibility that various cytokines in FBS may affect the results cannot be excluded. Serum-free culture condition is difficult to maintain in our cell model because our previous data showed that ≥5 days were needed before methylation of HBV cccDNA was induced ( 39 ). Other related studies also used similar study design with serum in culture media ( 16 , 30 ) and it is hypothesized that possible effect of cytokines may have been adjusted by comparison with the control with same culture condition (except for IFN).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Moon et al [ 175 ] has suggested that miR-20a can act in an epigenetic manner and promote methylation of cccDNA. They found that AGO2-miR-20a binding to the cccDNA may recruit DNMT3 to silence gene expression; however, further studies are needed to confirm the exact mechanism.…”
Section: Regulatory Noncoding Rnasmentioning
confidence: 99%